Picture Fuzzy Bzier Surface Approximation - Ahmad N.A.; Zulkifly M.I.E. (American Institute of Physics, 2025)
Surface modeling is an effective method that is frequently employed in industry. In this paper, approximation of picture fuzzy Bzier surface is shown where the control net of picture fuzzy relation is determined by concept of picture fuzzy set. Afterwards, the control net and the Bzier function are blended to generate picture fuzzy Bzier surface. At the end of this studies, picture fuzzy Bzier surface consist the positive, neutral, negative, and refusal membership surface is visualized. Some numerical example of picture fuzzy Bzier surface approximation and their respective properties are also shown. ? 2024 American Institute of Physics Inc.. All rights reserved.